THE ORIGINS OF THE MEXICAN STEEL INDUSTRY. CONTI-NUITIES AND CHANGES IN TECHNOLOGY IN THE NINETEENTH CENTURY (Tzintzun, Revista de Estudios Históricos, 2016)
This article discusses the historical development of the firs ironworks that werefounded in Mexico in the nineteenth century. Special emphasis is plaed on theevolution of the ironworks in the company named Nuestra Señora de Guadalupe,established by the mineralogist Andres Manuel del Rio in Coalcomán in 1805 andthe one in Piedras Azules built in Durango in 1826. Also looks at other foundriesthat were established in the present states of Jalisco, Guanajuato, Hidalgo, Morelosand Oaxaca. The leitmotif of the cases studied is the continuities and changes intechnology that were used in foundry systems and benefit of ferrous materials. Italso addresses the use of iron in the development of agricultural tools for the extractionof minerals, incluiding the mills that were used in sugar mills.
Keywords: Foundries; steel industry; iron